Global class Japanese SMEs - Kurosaki, Makoto 1944-; Greenberg, Larry (2017)
"Thirty years have passed since Japan emerged on the global stage as the second largest economy quickly moving upwards. More than twenty years have passed since the bubble burst, wiping away inflated dreams of Japan as Number One. The Cold War ended and China has overtaken Japan as Number Two. The digital revolution has come and IoT is changing everything. And yet Japan remains near the top as the third richest economy in the world despite the fallout from the scandals and disappointing performance from some of Japan's former giants"--Back cover.
World leaders employing traditional technologies : five companies : "we're not trying to be Toyota" -- Specialization is the key to success : a look at five companies : "we won't go as far as discounting prices just to make a sale" -- Four companies taking on the world with highly-advanced technologies : undaunted by domestic harassment -- Controlling niche markets inaccessible to big firms : six companies : "no need for an administrative department" -- Winning with "business category changes" that capitalize on expertise : four companies, including one that "will not move the operational core to China."
Translation of: Sekai ni kantaru chusho kigyo.
Includes bibliographical references (pages 167-169)
Japan Foundation
Text translated into English from Japanese.
Keywords: Small business -- Japan